Electrospinning: New Strategies for the Treatment of Skin Melanoma - Mancipe, Javier M. A.; Lobianco, Franz A.; Dias, Marcos Lopes; da Silva Moreira Thiré, Rossana Mara (Mini Reviews in Medicinal Chemistry, 2022)
Recent studies have shown a significant growth of skin cancer cases in northern regions of the world, in which its presence was not common. Skin cancer is one of the cancers that mostly affects the world’s population, ranking fifth in studies conducted in the United States (USA). Melanoma is cancer that has the highest number of deaths worldwide since it is the most resistant skin cancer to current treatments. This is why alternatives for its treatment has been investigated considering nanomedicine concepts. This study approaches the role of this field in the creation of promising electrospun devices, composed of nanoparticles and nanofibers, among other structures, capable of directing and/or loading active drugs and/or materials with the objective of inhibiting the growth of melanoma cells or even eliminating those cells.
Keywords: Skin melanoma